Monocytes to high-density lipoproteins ratio as an indicator of inflammation and oxidative stress in patients with various conditions of the gallbladder - Strilchuk, Larysa (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. The monocytes to high-density lipoproteins ratio (M/HDL) is known as an integral indicator of inflammation, oxidative stress and lipid accumulation, which allows its use in the assessment and prediction of a number of diseases. Purpose: to determine the clinical significance of M/HDL according to the literature and to establish its changes and correlations. Materials and methods. We made a literature search in the Pubmed database and domestic sources, and analyzed data of 1190 outpatients with various diagnoses and 116 inpatients with unstable angina (UA). Digital data were statistically processed with Statistica 6.0. Results and discussion. Elevated M/HDL is associated with the development of atrial fibrillation after coronary artery bypass grafting, hospital mortality, and all-cause mortality. M/HDL can be a criterion of inflammation and oxidative stress, as well as a predictor of the severity of coronary heart disease and the risk of cardiovascular events. According to own data, in 1190 outpatients the average level of M/HDL was 6.50 ± 0.21. The increase in the M/HDL ratio occurred in parallel with an increase in the number of blood basophils, the development of intrahepatic cholestasis, increased endogenous intoxication, decreased total cholesterol and fasting blood glucose, and diastolic left ventricular dysfunction. In patients with UA M/HDL averaged 5.41 ± 0.40. An increase in the M/HDL ratio was associated with male gender, a decrease in total cholesterol and fasting blood glucose, and lower integrative hematologic markers of immune reactivity. The M/HDL was maximal in patients with bent gallbladder body, which was accompanied by the elevated values of very low density lipoproteins cholesterol (0.80 ± 0.10 mmol/l), triglycerides (1.76 ± 0.21 mmol/l), both Castelli indices and lower high-density lipoprotein cholesterol. An inverse correlation of M/HDL with left ventricular ejection fraction was found in patients with intact gallbladder. Conclusions. 1. M/HDL is a valuable marker of atherosclerosis and inflammation. 2. M/HDL was maximal in patients with bent gallbladder body, which was accompanied by dyslipidemia. 3. The inverse correlation of M/HDL with left ventricle ejection fraction in case of intact gallbladder and direct correlation with the aorta diameter in patients with cholecystitis confirm the association of the increase of this ratio with the unfavorable course of cardiovascular diseases. 4. In patients with UA and intact gallbladder or cholelithiasis M/HDL correlated with the nuclear index of intoxication.